Clinical predictors of successful vaginal myomectomy for prolapsed pedunculated uterine leiomyoma - AYDIN, SERDAR; Aydın, SERDAR; MARAŞLI, MUSTAFA; Göksever, Çelik; BAKAR, RABIA ZEHRA; MARASLI, MUSTAFA; BAKAR, RABİA ZEHRA (My University, 2018)
Objective: Uterine leiomyomas are the most common pelvic tumor in women. The calculated prevalence of prolapsed pedunculated leiomyoma was 2.5% in patients who underwent surgery. Although vaginal removal is safe and effective, hysterectomy demand is questionable. We aimed to analyze the association between patient characteristics, clinical features of prolapsed pedunculated submucosal leiomyoma, and the probability of successful vaginal myomectomy. Material and Methods: This study was conducted in 35 women who presented with prolapsed pedunculated uterine leiomyoma. Patients were grouped according to the treatment procedure, either vaginal myomectomy or hysterectomy. Results: Hysterectomy was performed in 14 patients and vaginal myomectomy was performed in 21 women. The mean ages and menopausal status were similar. Parity was higher in the hysterectomy group (p=0.02). The preoperative hematocrit value of patients undergoing vaginal myomectomy was significantly lower (p=0.04). There was no significant difference between the groups regarding the largest leiomyoma diameter. However, the median calculated leiomyoma volume was lower in the vaginal myomectomy group (p=0.04). None of the variables were independently associated with successful vaginal myomectomy on multivariable logistic regression analysis. Conclusion: The feasibility and choice of vaginal myomectomy is associated with low parity, absence of coexisting leiomyoma, high volume of leiomyoma estimated via ultrasound measurement, and severe anemia. (J Turk Ger Gynecol Assoc 2018; 19: 146-50) Keywords: Leiomyoma, prolapsed pedunculated submucosal leiomyoma, vaginal myomectomy, hysterectomy